Papillary cannulation and sphincterotomy techniques at ERCP: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline - Testoni, Pier Alberto; Mariani, Alberto; Aabakken, Lars; Arvanitakis, Marianna; Bories, Erwan; Costamagna, Guido; Devière, Jacques; Dinis-Ribeiro, Mario; Dumonceau, Jean-Marc; Giovannini, Marc; Gyokeres, Tibor; Hafner, Michael; Halttunen, Jorma; Hassan, Cesare; Lopes, Luis; Papanikolaou, Ioannis S.; Tham, Tony C.; Tringali, Andrea; van Hooft, Jeanin; Williams, Earl J. (Endoscopy, 2016)
This Guideline is an official statement of the European Society of Gastrointestinal Endoscopy (ESGE). It provides practical advice on how to achieve successful cannulation and sphincterotomy at minimum risk to the patient. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was adopted to define the strength of recommendations and the quality of evidence.Main recommendations1 ESGE suggests that difficult biliary cannulation is defined by the presence of one or more of the following: more than 5 contacts with the papilla whilst attempting to cannulate; more than 5 minutes spent attempting to cannulate following visualization of the papilla; more than one unintended pancreatic duct cannulation or opacification (low quality evidence, weak recommendation).2 ESGE recommends the guidewire-assisted technique for primary biliary cannulation, since it reduces the risk of post-ERCP pancreatitis (moderate quality evidence, strong recommendation).3 ESGE recommends using pancreatic guidewire (PGW)-assisted biliary cannulation in patients where biliary cannulation is difficult and repeated unintentional access to the main pancreatic duct occurs (moderate quality evidence, strong recommendation). ESGE recommends attempting prophylactic pancreatic stenting in all patients with PGW-assisted attempts at biliary cannulation (moderate quality evidence, strong recommendation).4 ESGE recommends needle-knife fistulotomy as the preferred technique for precutting (moderate quality evidence, strong recommendation). ESGE suggests that precutting should be used only by endoscopists who achieve selective biliary cannulation in more than 80 % of cases using standard cannulation techniques (low quality evidence, weak recommendation). When access to the pancreatic duct is easy to obtain, ESGE suggests placement of a pancreatic stent prior to precutting (moderate quality evidence, weak recommendation).5 ESGE recommends that in patients with a small papilla that is difficult to cannulate, transpancreatic biliary sphincterotomy should be considered if unintentional insertion of a guidewire into the pancreatic duct occurs (moderate quality evidence, strong recommendation).In patients who have had transpancreatic sphincterotomy, ESGE suggests prophylactic pancreatic stenting (moderate quality evidence, strong recommendation).6 ESGE recommends that mixed current is used for sphincterotomy rather than pure cut current alone, as there is a decreased risk of mild bleeding with the former (moderate quality evidence, strong recommendation).7 ESGE suggests endoscopic papillary balloon dilation (EPBD) as an alternative to endoscopic sphincterotomy (EST) for extracting CBD stones < 8 mm in patients without anatomical or clinical contraindications, especially in the presence of coagulopathy or altered anatomy (moderate quality evidence, strong recommendation).8 ESGE does not recommend routine biliary sphincterotomy for patients undergoing pancreatic sphincterotomy, and suggests that it is reserved for patients in whom there is evidence of coexisting bile duct obstruction or biliary sphincter of Oddi dysfunction (moderate quality evidence, weak recommendation).9 In patients with periampullary diverticulum (PAD) and difficult cannulation, ESGE suggests that pancreatic duct stent placement followed by precut sphincterotomy or needle-knife fistulotomy are suitable options to achieve cannulation (low quality evidence, weak recommendation).ESGE suggests that EST is safe in patients with PAD. In cases where EST is technically difficult to complete as a result of a PAD, large stone removal can be facilitated by a small EST combined with EPBD or use of EPBD alone (low quality evidence, weak recommendation).10 For cannulation of the minor papilla, ESGE suggests using wire-guided cannulation, with or without contrast, and sphincterotomy with a pull-type sphincterotome or a needle-knife over a plastic stent (low quality evidence, weak recommendation).When cannulation of the minor papilla is difficult, ESGE suggests secretin injection, which can be preceded by methylene blue spray in the duodenum (low quality evidence, weak recommendation).11 In patients with choledocholithiasis who are scheduled for elective cholecystectomy, ESGE suggests intraoperative ERCP with laparoendoscopic rendezvous (moderate quality evidence, weak recommendation). ESGE suggests that when biliary cannulation is unsuccessful with a standard retrograde approach, anterograde guidewire insertion either by a percutaneous or endoscopic ultrasound (EUS)-guided approach can be used to achieve biliary access (low quality evidence, weak recommendation). 12 ESGE suggests that in patients with Billroth II gastrectomy ERCP should be performed in referral centers, with the side-viewing endoscope as a first option; forward-viewing endoscopes are the second choice in cases of failure (low quality evidence, weak recommendation). A straight standard ERCP catheter or an inverted sphincterotome, with or without the guidewire, is recommended by ESGE for biliopancreatic cannulation in patients who have undergone Billroth II gastrectomy (low quality evidence, strong recommendation). Endoscopic papillary ballon dilation (EPBD) is suggested as an alternative to sphincterotomy for stone extraction in the setting of patients with Billroth II gastrectomy (low quality evidence, weak recommendation).In patients with complex post-surgical anatomy ESGE suggests referral to a center where device-assisted enteroscopy techniques are available (very low quality evidence, weak recommendation).